The use of black liquor and nano-graphene oxide in urea formaldehyde adhesive to improve the mechanical and physical properties of particleboard - Mostafa Yahyavi (Regional Information Center for Science and Technology (RICeST), 2017)
Abstract The aim of this research is the possibility of using black liqour and nano Graphene oxide (GO) for making three-layer particle board. In this study, the amount of black liqour was as 0, 10, 20 and 30 percent and Graphene oxide was 0, 0.25 and 0.5 percent (based on oven dried weight of UF). Wood particles was pressed with using a laboratory hydraulic press. Mechanical and physical properties (modulus of rupture, modulus of elasticity, internal bonding, water absorption and thickness swelling after 2 and 24h soaking in water) of the produced boards were measured according to EN standards. The effect of each of the variables was studied on the properties and analyzed at 95 percent with using SPSS software and variance analysis factorial design. The results showed that increasing black liqour resulted in decreasing the modulus of rupture, modulus of elasticity and internal bonding. The results also indicated that water absorption and thickness swelling after 2 and 24h soaking in water increased with increased black liqour and Graphene oxide percent. The results show that increasing of nano ghraphen resulted in increasing modulus of rupture, modulus of elasticity and internal bonding.